The econometric analysis of the relationships among the investment saving and growth in Turkey and selected Latin American countries - Sarıdoğan, Ercan (My University, 2006)
THE ECONOMETRIC ANALYSIS OF THE RELATIONSHIPS AMONG THE INVESTMENT SAVING AND GROWTH IN TURKEY AND SELECTED LATIN AMERICAN COUNTRIES ÖZET Bu tezin temel amacı, makroekonomik değişken olarak, tasarruf, yatırım ve ekonomik büyüme arasındaki ilişkiyi incelemektir. Değişkenler arasındaki ilişkiyi incelemenin temel sebebi, hangi değişkenin anahtar değişken olduğunu ortaya çıkarmaktır. Eğer anahtar değişkeni tespit edersek, daha uygun ve etkin iktisat politikaları tasarımı yapılabilecektir. Temel olarak, Türkiye, Arjantin, Brezilya, Meksika ve Şili ekonomileri incelenmiştir. Uygulama kısmında, zaman serisi ve panel zaman serisi tekniklerini kullanılarak 1950-2004 dönemi için inceleme yapılmıştır. Ortaya çıkan temel sonuç, değişkenler gerek ülke bazında gerekse panel olarak yakın bir ilişkiye sahip olup, uzun dönemde eşbütünleşiktir (cointegrated). Yatırım ve ekonomik büyüme değişkenleri göreceli olarak, tasarruflar üzerinde daha fazla etkiye sahiptir. Ekonomik politika tasarım süreçlerinde bu güne kadar, iç ve dış tasarruf sahipleri için tasarruf koşullarının iyileştirilmesi üzerine odaklanıldı. Ne var ki, ekonomi politikaların başarısı için tasarruf koşullarının iyileştirilmesi gerekli olsa bile yeterli olamamaktadır. Bu sebeple, ekonomik politika tasarımlarında, yatırımlar ve ekonomik büyümeye direkt hedeflemek, dolayısıyla da, iç ve dış yatırımcılar için, yatırım ve ekonomik büyümenin iklimini/ koşullarını/ faktörlerini iyileştirmeye odaklanmak çok önemlidir. Bu sebeple yatırımcılar için kârlılık koşullarını, teknoloji, araştırma ve geliştirme, beşeri sermaye açısından rekabet üstünlüğünü , ekonomik ve politik istikrarı ve diğer kurumsal faktörleri iyileştirmek politika tasarımlarında öncelikli olarak yer almalıdır. Sonuç olarak, politika tasarım süreçlerinde, yatırım, ekonomik büyüme ve gelişmenin yukarda belirtilen rekabet odaklı parametrelerini incelemeye, ortaya çıkarmaya ve iyileştirmeye odaklanılmalıd THE ECONOMETRIC ANALYSIS OF THE RELATIONSHIPS AMONG THE INVESTMENT SAVING AND GROWTH IN TURKEY AND SELECTED LATIN AMERICAN COUNTRIES ERCAN SARIDOĞAN

Main aim of this thesis is to investigate the interaction among the saving, investment and growth to find out the key variables in order to design efficient and appropriate economic policies by using the time series and panel time series econometric techniques for the period 1950-2004. We mainly focused on the countries Turkey, Argentina, Mexico, Brazil, and Chile which have been erratic growth performance for years. The results based on the time series and panel time series econometric techniques shows that these variables have closer relationship in all countries and cointegrated in the long run both in country-level and in panel group-level. We can conclude that investment and economic growth variables are relatively more effective on saving than saving does. In economic policy design processes it has been focused on improvement saving conditions for foreign and domestic savers so far, however the economic policy for improving saving conditions is essential but not enough to ensure investment and economic growth. It would be very important to consider investment and economic growth directly when designing economic policies. So that, it is essential to focus on the improvement the climate/ conditions/ factors of the investment and economic growth for foreign and domestic investors by improving the conditions/ climate for the most important macroeconomic factors stimulating investment and economic growth that are profitability, advantages of competitiveness in terms of technology, research and development processes, costs, skilled-educated human capital, political and economic stability and other improved institutional parameters. As a result, it should be focused to find out and improve these competitiveness-oriented parameters of investment, economic growth and development when designing economic policies.
Keywords: Ekonomik Büyüme; Makroekonomi; Türkiye_Ekonomi Politikası_Latin Amerika